ANTIMICROBIAL POTENTIAL OF FICUS BENGALENSIS AERIAL ROOTS - RAKESH K. SINGH; GEETA WATAL (International Journal of Pharma and Bio Sciences, 2010)
Herbal preparations of Ficus bengalensis L. (Moraceae) have been considered as safe, effective and economical for various ailments in Indian traditional system of medicine. The present study was aimed to scientifically explore the antimicrobial potential of F. bengalensis aerial roots. Effect of variable concentrations of aqueous and hexane extracts of F. bengalensis aerial roots was studied on three different non-pathogenic bacterial strains. All the three different concentrations of 25, 50 and 75 mg/ml of aqueous and hexane aerial root extracts showed sustained activity against all the bacterial strains. The sensitivity of the extracts against each bacterial strain was determined by identifying the diameter of inhibition zone (DIZ) for each concentration and the highest activity was observed against Staphylococcus aureus for each of the three concentrations in case of both the extracts.